Formulation of maximum weight percent gain of wood impregnated with resin considering cell wall swelling and resin concentration distribution: in the impregnation of six softwood species with phenol formaldehyde resin - Soichi Tanaka; Masako Seki; Mitsuru Abe; Tsunehisa Miki (Journal of Wood Science)
Abstract Weight percent gain (WPG) is used as an index of the quantity of impregnated resin into wood. It is well‐known that the maximum value of WPG is roughly calculated using the volume of cell lumen included in wood. In this study, we proposed the theoretical formula that calculates the maximum value of WPG (W-value), with higher accuracy by considering the cell wall swelling and resin concentration distribution as well as the cell-lumen volume. In this paper, the WPG of wood for six softwood species was measured after the injection with phenol–formaldehyde resin solution and after the subsequent conditioning and drying. The measured WPG values after each process were successfully explained by the W-value calculated using the theoretical formula. It was suggested from the calculation that the WPG was greatly influenced by the cell wall swelling and by the difference in solution concentration between the cell lumen and the transient pore in the cell wall. The influences were also suggested to be larger for wood with higher density.